Evaluating Phospholipid‐Functionalized Gold Nanorods for In Vivo Applications. Issue 13 (8th March 2021) - Roach, Lucien; Booth, Mary E.; Ingram, Nicola; Paterson, Daniel A.; Batchelor, Damien V. B.; Moorcroft, Samuel C. T.; Bushby, Richard J.; Critchley, Kevin; Coletta, P. Louise; Evans, Stephen D.
Abstract: Gold nanorods (AuNRs) have attracted a great deal of attention due to their potential for use in a wide range of biomedical applications. However, their production typically requires the use of the relatively toxic cationic surfactant cetyltrimethylammonium bromide (CTAB) leading to continued demand for protocols to detoxify them for in vivo applications. In this study, a robust and facile protocol for the displacement of CTAB from the surface of AuNRs using phospholipids is presented. After the displacement, CTAB is not detectable by NMR spectroscopy, surface‐enhanced Raman spectroscopy, or using pH‐dependent ζ‐potential measurements. The phospholipid functionalized AuNRs demonstrated superior stability and biocompatibility (IC50  > 200 µg mL −1 ) compared to both CTAB and polyelectrolyte functionalized AuNRs and are well tolerated in vivo. Furthermore, they have high near‐infrared (NIR) absorbance and produce large amounts of heat under NIR illumination, hence such particles are well suited for plasmonic medical applications. Abstract : Phospholipids offer a robust, inexpensive, and facile method for the displacement of the toxic surfactant cetyltrimethylammonium bromide (CTAB) from gold nanorods (AuNRs). Removal of CTAB is of considerable importance for the biological application of AuNRs. Phospholipid AuNRs demonstrated superior stability compared to CTAB and polyelectrolyte functionalizations. Both in vitro and in vivo models demonstrated that they are highly biocompatible.